(untitled) (Communications in Computational Physics, 2018)
In this study, an N-body simulation code was developed for self-gravitating systems with a limited first-order post-Newtonian approximation. The code was applied to a special case in which the system consists of one massive object and many low-mass objects. Therefore, the behavior of stars around the massive black hole could be analyzed. A graphics processing unit (GPU) was used to accelerate the code execution, and it could be accelerated by several tens of times compared to a single-core CPU for N ≃104 objects.